Validity and reliability of geriatric depression scale-15 (short form) in Turkish older adults - Busra Durmaz; Pinar Soysal; Hulya Ellidokuz; Ahmet Turan Isik (İstanbul Kuzey Klinikleri, 2018)
INTRODUCTION[|]The present study aimed to assess the validity and reliability of Geriatric Depression-15 Scale (GDS-15) in Turkish older adults and to compare the results with Diagnostic and Statistical Manual of Mental Disorders-fifth edition (DSM-5) depression criteria.[¤]METHODS[|]A total of 329 outpatients were enrolled. In the first step, the patients underwent the Mini-Mental State Examination. After assessing whether the patients meet the diagnosis of depression based on DSM-5 diagnostic criteria, another researcher applied the long form of GDS. After sorting the items of short form out of the long form, two separate scores were obtained. The scores of GDS-30 and GDS-15 scales were compared with the scores of DSM-5.[¤]RESULTS[|]The correlation of GDS-30 with GDS-15 was r=0.966 (p<0.001). The analysis performed considering DSM-5 criteria revealed that the sensitivity, specificity, positive predictive value, and negative predictive value of GDS-15 in determining depression were 92%, 91%, 76%, and 97%, respectively, when the cutoff value was taken as ≥5. The area under the receiver operating characteristics curve [95% confidence interval (CI)] was 0.97 (95% CI=0.947–0.996) for GDS-15 (p<0.001). The Cronbach alpha coefficient for the total scale was 0.920.[¤]DISCUSSION AND CONCLUSION[|]GDS-15, just as GDS-30, is a beneficial scale in determining depression in older adults. This study provides an evidence for the validity and reliability of GDS-15 in Turkish elderly population and primary care centers.[¤]